Impact of Duration of Untreated Psychosis on Cognitive Function in Schizophrenia - Rina Krismiati Gani; Erikavitri Yulianti; Ifa Tunisya (Jurnal Psikiatri Surabaya, 2021)
Background: Schizophrenia is a chronic and serious clinical syndrome with very aggravating psychopathology involving perception, cognition, emotion, and behaviour. Currently, cognitive dysfunction is seen as a core disorder of schizophrenia. Duration of Untreated Psychosis (DUP) refers to the period from the onset of psychotic symptoms to the first adequate administration of antipsychotics.Aims: This review aims to analyse the impact of DUP on cognitive function in schizophrenia.Methods: PubMed and Google Scholar were searched using the following keyword: (cognitive function) and (neurodevelopmental OR neurotoxicity hypothesis) and (duration of untreated psychosis or DUP) and (schizophrenia or psychosis or psychotic) using the journal publication filter for the 2014-2020 issue. We also used textbooks published in the last 10 years and were related to writing themes.Review: There are two different opinions about the impact of DUP on the cognitive function of schizophrenic patients: (1) the neurodevelopmental hypothesis says there is no impact of the length of DUP on the cognitive function of schizophrenic patients; (2) the neurotoxicity hypothesis says the length of the DUP will impact the patient's cognitive function. Despite differences of opinion about the impact of DUP on cognitive function in schizophrenia, early intervention in schizophrenic patients is important because DUP is associated with worse general disease symptoms, lower likelihood of remission, more severe positive and negative symptoms, and worse social functioning and overall outcomes.Summary: There are differences of opinion about the impact of DUP on cognitive function in schizophrenic patients.